Radical optic flow induces vergence eye movements with ultra-short latencies - Busettini, C; Masson, G S; Miles, F A (Nature (London), 1997)
An observer moving forwards through the environment experiences a radial pattern of image motion on each retina. Such patterns of optic flow are a potential source of information about the observer's rate of progress, direction of heading and time to reach objects that lie ahead. As the viewing distance changes there must be changes in the vergence angle between the two eyes so that both foveas remain aligned on the object of interest in the scene ahead. Here we show that radial optic flow can elicit appropriately directed (horizontal) vergence eye movements with ultra-short latencies (roughly 80 ms) in human subjects. Centrifugal flow, signalling forwards motion, increases the vergence angle, whereas centripetal flow decreases the vergence angle. These vergence eye movements are still evident when the observer's view of the flow pattern is restricted to the temporal hemifield of one eye, indicating that these responses do not result from anisotropies in motion processing but from a mechanism that senses the radial pattern of flow. We hypothesize that flow-induced vergence is but one of a family of rapid ocular reflexes, mediated by the medial superior temporal cortex, compensating for translational disturbance of the observer.